Intraarticular osteotomy for adult Madelung deformity: Case report - Pedro C. Cavadas; Juan Ramón Sanz Gimenez-Rico; Ana Ruo Lan Cavadas (JPRAS Open)
Madelung deformity is a hemi-epiphyseal dysplasia of the radioulnar axis. The prominent feature is radial deformity secondary to premature closure of the volar-ulnar side of the distal radial physics. The distal radius is malaligned with excessive ulnar and volar tilt, shortening and concomitant ulna plus deformity.Adults presenting most frequently complain of pain, limited wrist motion and poor cosmesis. Surgical indications in adult patients are severe pain and/or limitation of wrist motion. Current surgical treatments consist of various types of extraarticular osteotomies to improve the alignment of the distal radius epiphysis, without addressing the intrinsic deformity of the articular surface itself.The authors present a novel technique of intraarticular osteotomy in an adult patient with severely deformed articular distal radial articular facets. To the best of the authors’ knowledge, no similar technique has been previously described in the literature.